Platelet-bound C4d, low C3 and lupus anticoagulant associate with thrombosis in SLE. Issue 1 (30th March 2019) - Petri, Michelle A; Conklin, John; O'Malley, Tyler; Dervieux, Thierry
Abstract : Background: Low C3 and lupus anticoagulant (LAC) are known risk factors for thrombosis in SLE. We evaluated the association between C4d products deposited on platelets (PC4d) and thrombosis in SLE. Antiphosphatidyl serine/prothrombin (PS/PT) complex antibody was also evaluated as an alternative to LAC. Methods: This was a cross-sectional analysis of 149 consented patients with SLE (mean age: 47±1 years, 86% female) classified with (n=16) or without (n=133) thrombotic events in the past 5 years. Abnormal PC4d (≥20 units) was measured using flow cytometry. LAC and C3 were measured using dilute Russell's viper venom time (>37 s) and immunoturbidimetry, respectively. Anti-PS/PT antibody status (IgG) was measured by immunoassay. Statistical analysis consisted of logistic regression and calculation of OR estimates with 95% CI. Results: Abnormal PC4d (OR=8.4,  95% CI 2.8 to 24.8), low C3 (OR=9.5,  95% CI 3.0 to 30.3), LAC (OR=5.4,  95% CI 1.3 to 22.3) and anti-PS/PT IgG (OR=3.4,  95% CI 1.2 to 9.7) status associated with thrombosis (p<0.05). Cumulatively, the presence of PC4d, low C3 and LAC abnormalities as a composite risk score was higher in the presence of thrombosis (1.93±0.25) than in its absence (0.81±0.06) (p<0.01). Each unit of this composite risk score yielded an OR of 5.2 (95% CI 2.5 to 10.7) to have thrombosis (p<0.01). The composite risk score with anti-PS/PT antibody status instead of LAC also associated with thrombosis (p<0.01). Conclusion: A composite risk score including PC4d, low C3 and LAC was associated with recent thrombosis and acknowledges the multifactorial nature of thrombosis in SLE.